Lucia Joyce To Dance in the Wake. Book review. - Baymiller, Joanna (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Lucia Joyce, James Joyce's only daughter.
Lucia Joyce: To Dance in the Wake. Carol Loeb Shloss, Bloomsbury Publishing, 2004.